Electromyographic evaluation of upper extremity muscles during forehand and backhand table tennis drives - Maheshwari, A.; Pal, S.; Pandey, G. (Journal of Physical Education and Sport, 2023)
This study aims to identify the Electromyographic comparison of upper extremity muscles during table tennis drive (forehand and backhand topspin drive). The idea behind conducting this research was to figure out the relative contribution of selected muscles of the upper extremities while performing forehand and backhand Table Tennis Drives. Many studies have been published before where EMG analysis was done on Forehand drive. The present study uses a comparative approach to observe meaningful and statistically valid differences in EMG analysis while performing Forehand and Backhand Drives. Observed Root mean square (RMS) values provided by EMG-analyzer were taken into consideratio for analysis. For the compilation of the study a total of Fifteen (15) female university table tennis players who were right-hand dominant (age 21.2±2.3 years, height 161.9±7.8 cm and body mass 62.2±6.9 kg) and had a minimum of six years of playing experience selected as sample for this study. The selected upper extremity muscles based on reviews were flexor carpi radialis (FCR), extensor carpi radials (ECR), biceps brachii (BB), pectoralis major (PM), anterior deltoid (AD) and stomach oblique (SO). The EMG signals data was collected through Wireless surface electromyography having eight channels. A fixed window of 100 ms was used to calculate the RMS (root mean square) value of the signals. One-way ANOVA was used as a statistical technique for comparison and a separate post-hoc test was conducted for pairwise comparison. The study concludes that Pectoralis Major and Anterior Deltoid muscles are important factors for forehand and backhand topspin drive.